2011
DOI: 10.1074/jbc.m110.200071
|View full text |Cite
|
Sign up to set email alerts
|

Yeast 3-Phosphoinositide-dependent Protein Kinase-1 (PDK1) Orthologs Pkh1–3 Differentially Regulate Phosphorylation of Protein Kinase A (PKA) and the Protein Kinase B (PKB)/S6K Ortholog Sch9

Abstract: Pkh1, -2, and -3 are the yeast orthologs of mammalian 3-phosphoinositide-dependent protein kinase-1 (PDK1). Although essential for viability, their functioning remains poorly understood. Sch9, the yeast protein kinase B and/or S6K ortholog, has been identified as one of their targets. We now have shown that in vitro interaction of Pkh1 and Sch9 depends on the hydrophobic PDK1-interacting fragment pocket in Pkh1 and requires the complementary hydrophobic motif in Sch9. We demonstrated that Pkh1 phosphorylates S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 52 publications
2
75
0
Order By: Relevance
“…In S. cerevisiae, it has been shown that Thr 241 in the Tpk1 activation loop is phosphorylated by Pkh1 immediately after the catalytic subunit is synthesized [5]. Besides Tpk1, an uncharacterized residue on Tpk2 and Thr 242 in Tpk3 are also phosphorylated in vivo by Pkh1 with different efficiency.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In S. cerevisiae, it has been shown that Thr 241 in the Tpk1 activation loop is phosphorylated by Pkh1 immediately after the catalytic subunit is synthesized [5]. Besides Tpk1, an uncharacterized residue on Tpk2 and Thr 242 in Tpk3 are also phosphorylated in vivo by Pkh1 with different efficiency.…”
Section: Discussionmentioning
confidence: 98%
“…This phosphorylation was independent of nitrogen or glucose availability [5]. We have shown that Pkh1 inactivation reduces the interaction between Tpk1 and the regulatory subunit Bcy1 without affecting the specific kinase activity [6].…”
Section: Tpk1 Phosphorylation On Ser 179 Occurs During the Transitionmentioning
confidence: 97%
See 2 more Smart Citations
“…These studies have shown that the Pkhs regulate a wide variety of cellular functions in S. cerevisiae, including cell wall integrity (21), sphingolipid biosynthesis (22,23), endocytosis (24), eisosome formation (25,26), flippase activity (22), and RNA metabolism (25). In S. cerevisiae, six key Pkh substrates have been identified, i.e., the AGC kinases protein kinase A (PKA), Pkc1, Ypk1/2, and Sch9 as well as a component of the eisosome, Pil1 (26)(27)(28)(29).…”
mentioning
confidence: 99%